2012
DOI: 10.1093/nar/gks722
|View full text |Cite
|
Sign up to set email alerts
|

Histone dosage regulates DNA damage sensitivity in a checkpoint-independent manner by the homologous recombination pathway

Abstract: In eukaryotes, multiple genes encode histone proteins that package genomic deoxyribonucleic acid (DNA) and regulate its accessibility. Because of their positive charge, ‘free’ (non-chromatin associated) histones can bind non-specifically to the negatively charged DNA and affect its metabolism, including DNA repair. We have investigated the effect of altering histone dosage on DNA repair in budding yeast. An increase in histone gene dosage resulted in enhanced DNA damage sensitivity, whereas deletion of a H3–H4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 106 publications
(165 reference statements)
5
54
0
Order By: Relevance
“…Such Hinfp deficiency-related replicative stress is likely to induce genomic instability and DNA damage during S phase. Several studies in yeast have shown that removal or altered dosage of other core nucleosomal proteins H3 and H2B in addition to H4 creates numerous cell growth defects, increased sensitivity to DNA damage, and altered nucleosome positioning (48)(49)(50)(51)(52)(53)(54)(55). Recent findings also show that perturbations in normal nucleosome spacing compromise transcription and genome integrity, as well as predispose dividing cells to tumorigenesis (56).…”
Section: Discussionmentioning
confidence: 99%
“…Such Hinfp deficiency-related replicative stress is likely to induce genomic instability and DNA damage during S phase. Several studies in yeast have shown that removal or altered dosage of other core nucleosomal proteins H3 and H2B in addition to H4 creates numerous cell growth defects, increased sensitivity to DNA damage, and altered nucleosome positioning (48)(49)(50)(51)(52)(53)(54)(55). Recent findings also show that perturbations in normal nucleosome spacing compromise transcription and genome integrity, as well as predispose dividing cells to tumorigenesis (56).…”
Section: Discussionmentioning
confidence: 99%
“…The histone H3-R129E mutation weakens Asf1-H3 interaction without affecting the interaction between Asf1 and Rad53 (Agez et al 2007;Jiao et al 2012). In budding yeast, transcription of HHT2 contributes ∼85% of total H3 mRNA (Cross and Smith 1988;Liang et al 2012). We therefore introduced the HHT2-R129E mutation into our two-DSB system in the wild-type, asf1Δ, rtt101Δ, and rtt109Δ backgrounds.…”
Section: Degradation Of Rad53 Rescues the Recovery Defect Of Asf1δmentioning
confidence: 99%
“…Consistent with a central role in histone gene expression is the synthetic lethality observed upon loss of the individual SAGA subunits Spt8, Spt20, and Gcn5 with deletion of the histone transcriptional activator Spt10 (Chang and Winston 2013). Normal cell cycle progression and DNA repair require precise regulation of histone levels (Singh et al 2009;Singh et al 2010;Eriksson et al 2012;Liang et al 2012;Ghule et al 2014), therefore restoration of histone expression likely contributes to the restored cell cycle progression and growth upon DNA damage that we observe in gcn5D cells overexpressing RTS1.At the end of S phase, Wee1 phosphorylates H2B-Y40 at histone gene promoters to downregulate expression (Mahajan et al 2012), but a counteracting phosphatase is unknown. Future work should determine whether PP2A Rts1 directly dephosphorylates H2BY40ph as part of the mechanism of histone gene activation.…”
mentioning
confidence: 92%